2013
DOI: 10.1136/annrheumdis-2013-eular.1874
|View full text |Cite
|
Sign up to set email alerts
|

SAT0148 Short and Long-Term Biological Therapy in Refractory Uveitis of Behcet’S Syndrome. Multicenter Study of 108 Patients

Abstract: Objectives To assess response to biological therapy in uveitis associated to Behçet´s syndrome (BS) refractory to standard immunosuppressants (IS). Methods Study of 108 patients from 32 hospitals. All of them presented inadequate response to at least 1IS. Inflammation was evaluated according to SUN (Am J Ophthalmol 2005); macular thickness by optical coherence tomography (OCT). Results were expressed as mean±SD, or median [25t-75th(IQR)]. Comparisons were made between baseline and 1st week, 1st, 6th month, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The characteristics of these studies ( Bawazeer et al., 2010 ; Keino et al., 2011 ; Cantini et al., 2012 ; Okada et al., 2012 ; Al Rashidi et al., 2013 ; Bejerano et al., 2013 ; Calvo-Río et al., 2013 ; Hamuryudan et al., 2013 ; Mesquida et al., 2013 ; Calvo-Río et al., 2014 ; Interlandi et al., 2014 ; Takeuchi et al., 2014 ; Domínguez Casas et al., 2017 ; Fabiani et al., 2017 ; Degirmenci et al., 2018 ; El Garf et al., 2018 ; Martín-Varillas et al., 2018 ; Katsuyama et al., 2019 ; Yalcindag and Kose, 2019 ) were described in Table 1 and Supplementary Table 1 . The 18 articles comprised 968 patients in total and the number of patients in each study ranged from 11 to 164.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of these studies ( Bawazeer et al., 2010 ; Keino et al., 2011 ; Cantini et al., 2012 ; Okada et al., 2012 ; Al Rashidi et al., 2013 ; Bejerano et al., 2013 ; Calvo-Río et al., 2013 ; Hamuryudan et al., 2013 ; Mesquida et al., 2013 ; Calvo-Río et al., 2014 ; Interlandi et al., 2014 ; Takeuchi et al., 2014 ; Domínguez Casas et al., 2017 ; Fabiani et al., 2017 ; Degirmenci et al., 2018 ; El Garf et al., 2018 ; Martín-Varillas et al., 2018 ; Katsuyama et al., 2019 ; Yalcindag and Kose, 2019 ) were described in Table 1 and Supplementary Table 1 . The 18 articles comprised 968 patients in total and the number of patients in each study ranged from 11 to 164.…”
Section: Resultsmentioning
confidence: 99%
“…The changes of CMT were evaluated and analyzed in five studies ( Al Rashidi et al., 2013 ; Bejerano et al., 2013 ; Calvo-Río et al., 2013 ; Calvo-Río et al., 2014 ; Domínguez Casas et al., 2017 ). The pooled results suggested that CMT decreased by 112.70 μm, with a 95% CI of 72.8–153 μm, indicating significant difference.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation